High dead-space syringe use among people who inject drugs in Tijuana, Mexico. (May 2015) - Rafful, Claudia; Zule, William; González-Zúñiga, Patricia E.; Werb, Dan; Medina-Mora, María Elena; Magis-Rodriguez, Carlos; Strathdee, Steffanie A.
Abstract Background: High dead-space syringes (HDSS) are believed to confer an elevated risk of acquiring HIV and other blood-borne infections. Objectives: We identified prevalence and correlates of HDSS use among injection drug users (IDU) in Tijuana, Mexico, where syringe purchase and possession is legal without a prescription. Methods: Beginning in 2011, IDU who reported being 18 years or older and injected drugs within the last month were recruited into a prospective study. At baseline and semi-annually, 557 IDU underwent HIV-testing and interviewer-administered surveys. Logistic regression was used to identify correlates of using HDSS. Results: Of 557 IDU, 40% had ever used HDSS, mostly because no other syringe type was available (72%), or because they were easier to get (20%). Controlling for sex and age at first injection, use of HDSS was associated with cocaine as the first drug injected (Adjusted Odds Ratio [AOR]: 2.68; Confidence Interval 95% [CI]: 1.15–6.22), having been stopped or arrested by police (AOR: 1.84; 95% CI: 1.11–3.07), being deported from the US (AOR: 1.64; 95% CI:1.06–2.53), and believing it is illegal to carry syringes (AOR:1.78; 95% CI: 1.01–3.15). Conclusion: Use of HDSS is surprisingly common among IDU in Tijuana. Efforts are needed to expand coverage of low-dead space syringes through existing syringe exchange programs. Education is required to increase awareness of the harms associated with HDSS, and to inform IDU that syringe possession is legal across Mexico.